Production of Green Concrete Using Waste Carbonation Lime Residue from Sugar Factory (Journal of Civil Engineering Researchers, 2026)
This research investigates the possibility of producing green concrete using Carbonation Lime Residue (CLR), a waste by-product from the Naghsh-e Jahan Sugar Factory in Isfahan (Iran). The primary objective is to recycle this industrial waste by utilizing it as a partial replacement for cement in concrete production, aligning with waste management goals, environmental preservation, and economic benefits. Concrete samples were prepared with different percentages of CLR replacement (0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, and 40%) for cement, maintaining a constant water-to-cement ratio of 0.35. These samples were subjected to compressive strength tests (at 7, 28, and 56 days) and tensile strength tests (Brazilian method). The results indicated that both compressive and tensile strengths decrease with an increase in the replacement percentage. This reduction is primarily attributed to the presence of impurities and sugary substances in the CLR, as confirmed by SEM and EDX analyses. However, it was observed that up to a 25% replacement level, the reduction in compressive and tensile strengths was less than respectively 15% and 10%. This level of reduction is considered acceptable given the environmental and economic advantages derived from utilizing this waste material. Therefore, using waste CLR as a cement replacement in concrete up to 25% is deemed a practical and effective solution, particularly for non-structural applications or in regions near sugar factories, contributing to sustainable development and a circular economy.
Keywords: Green Concrete; Carbonation Lime Residue (CLR); Recycling; Cement Replacement; Compressive Strength; Sustainable Development